Pelatihan Pemanfatan Aplikasi Mendeley bagi Mahasiswa Prodi MPI STITNU Sakinah Dharmasraya dalam Penulisan Tugas Akhir - Kamsir, Rita Zahara; Fitri, Nidya; Andre, Lesis; Amin, Rafqi; Siska, Widia; Intan, Angel Sophia; Hasan, Alfadila; Agustian, Hesti; Anggraini, Widya Dwi; Mirdad, Jamal; Ariesta, Ariesta; Afriwes, Afriwes; Sagita, Avni; Hasibuan, Herianto (Civiliza Publishing, 2024)
The improvement of the completion of the final final assignment for the students of STITNU Sakinah Dharmasraya MPI prodi is necessary because to improve the academic quality of the students. The purpose of this training is to improve the knowledge and skills of students in applying the mandeley application in writing the final assignment. The training was conducted at STITNU Sakinah Dharmasraya Campus with a total of 43 students. Methods of collection using the method of observation. The analysis is studied using the lecture method and hands-on practice of operating the mandeley application. The results of this devotional activity to the Society showed an increase in the ability to operate the mandeley application in the completion of the final task. This PKM activity is expected to continue to be done to other students at STITNU Sakinah Dharmasraya in order to maintain the quality and academic culture of the campus.